Travel Behavior Characteristics Analysis Technology Based on Mobile Phone Location Data Methodology and Empirical Research - Yang, Fei; Yao, Zhenxing (Springer Nature Singapore : Imprint: Springer, 2022)
XXII, 217 p. 122 illus., 107 illus. in color.